Does the Belt and Road Initiative boost industrialization? Empirical evidence from African economies - Abas Omar Mohamed (Cogent Economics & Finance)
Exploiting the economic dividends of the mega-infrastructure investments related to the Belt and Road Initiative as a timely global South-South cooperation model, this study follows the New Structural Economics theory to examine the effects of the BRI membership on Africa’s industrialization. A panel fixed effects and Instrumental Variable (IV) estimation methods were employed to conduct an in-depth empirical analysis of BRI’s impacts on Africa’s industrialization. The study utilized country and firm-level datasets to provide comprehensive macro and micro empirical evidence for 51 African countries from 2000 to 2022. The baseline macro-level findings show that BRI membership and infrastructure investments promoted the aggregate industry value-added share of GDP in Africa. Moreover, the firm-level results provide solid empirical evidence by showing significant annual sales growth of manufacturing firms in African BRI member countries. However, juxtaposing various industry specification measurements, the results did not provide empirical evidence that BRI boosts the narrowly defined manufacturing value added. Meanwhile, consistently withstanding rigorous robustness and heterogenous checks, the study findings provide evidence-based practical policy recommendations for the African economies. Designating BRI as a 21st-century industrialization-led development model, these policy recommendations have overarching implications for achieving economic transformation goals listed in the African Union Agenda 2063.